Changes of the brain activities after chronic restraint stress in rats: A study based on 18F-FDG PET. (5th February 2018) - Wei, Kai; Bao, Weiqi; Zhao, Zhengxiao; Zhou, Weiyan; Liu, Jiaqi; Wei, Ying; Li, Mihui; Wu, Xiao; Liu, Baojun; Du, Yijie; Gong, Weiyi; Dong, Jingcheng
Highlights: CRS-induced depressive rats possessed increased peripheral inflammatory response. CRS decreased glucose metabolism in some brain regions, including limbic system. Increased peripheral inflammatory response and decreased brain activities could reflect the severity of CRS-induced depressive behaviors. Abstract: As a prevalent disease all over the world, changed functional activities and/or structures in many brain regions have been found in depression. In this study, 5-week chronic restraint stress (CRS) was performed to establish depression rat models, and 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) was used to detect brain functional activities. Our study found that CRS induced depressive behaviors and increased the expression of serum IL-6. After exposure to CRS, rats showed decreased glucose metabolism in the whole-brain and brain regions including left medial prefrontal and auditory cortices; right amygdala, cingulate cortex, olfactory and AcbCore/Shell; bilateral caudate putamen, dorsal hippocampi, insular and entorhinal cortices. Expression of serum IL-6 and glucose metabolism in most of the above brain regions were significantly correlated with the severity of some CRS-induced depressive behaviors. In conclusion, the increased peripheral inflammatory response and decreased brain functional activities might be the important pathogenesis of experimental depression induced by CRS, and could reflect the severity of depression to some extent.